A process evaluation of the 'Aware' and 'Supportive Communities' gambling harm-minimisation programmes in New Zealand. (31st August 2017) - Kolandai-Matchett, Komathi; Bellringer, Maria; Landon, Jason; Abbott, Max
Abstract: Background: The Gambling Act 2003 mandated a public health strategy for preventing and minimising gambling harm in New Zealand . Aware Communities and Supportive Communities are two public health programmes subsequently implemented nationwide. These programmes differed from common health promotion initiatives such as media or education campaigns as they were community-action based (requiring community involvement in programme planning and delivery). We carried out a process evaluation to determine their implementation effectiveness and inform improvement and future programme planning. Methods: Our qualitative dominant mixed methods design comprised analysis of over a hundred implementer progress reports (submitted July 2010 - June 2013), a staff survey and a staff focus group interview. Results: The programmes demonstrated capacity to not only achieve expected outcomes (e.g. enhanced community awareness about harmful gambling), but also to enhance social sustainability at the community level (e.g. established trustful relationships) and achieve some programme sustainability (e.g. community ownership over ongoing programme delivery). Conclusions: The evaluation noted the potential for a sustainable gambling harm-minimisation model. Community-action based harm-minimisation programmes offer programme sustainability potential which in turn offers funding cost-effectiveness when there are continual public health outcomes beyond initial funding. Although resource intensive, the community-action based approach enables culturally appropriate public health programmes suitable for societies where specific ethnic groups have higher gambling risk. Recognition of such harm-minimisation programmes' contribution to social sustainability is important considering the potential for broader public health outcomes (e.g. better life quality, lesser social problems) within socially sustainable societies.